2017 IEEE Power &Amp; Energy Society General Meeting 2017
DOI: 10.1109/pesgm.2017.8274447
|View full text |Cite
|
Sign up to set email alerts
|

Optimal distributed generation and reactive power allocation in electrical distribution systems

Abstract: Optimal and simultaneous siting and sizing of distributed generators and capacitor banks in distribution systems have attracted a lot of attention from distribution companies. The placement and capacity of these devices have direct effects on the system's performance. This paper presents a model for the simultaneous allocation of capacitor banks and distributed generation, which takes into account the stochastic nature of distributed generation. To solve the model presented, we propose an efficient hybrid meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
69
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 0 publications
0
69
0
2
Order By: Relevance
“…With respect to SG technologies, existing studies confirmed the feasibility and significance of DG in managing the balance between supply and demand [4]- [6]. Besides, the SG supports the bidirectional communication between consumers and grids via smart metering systems.…”
Section: Introductionmentioning
confidence: 95%
“…With respect to SG technologies, existing studies confirmed the feasibility and significance of DG in managing the balance between supply and demand [4]- [6]. Besides, the SG supports the bidirectional communication between consumers and grids via smart metering systems.…”
Section: Introductionmentioning
confidence: 95%
“…Microgrids are the solutions to incorporate several types of distributed Renewable Energy Sources (RESs), energy storage devices, Electric Vehicle (EV) charging stations, and different types of dynamic and nonlinear load, with the utility grid . The design and deployment of the conventional approach of a microgrid are usually done with the help of the Alternating Current (AC) system . The Direct Current (DC) microgrids are gaining attraction in real‐time implementation due to various advantages over AC microgrid like lack of need for synchronization, high power transfer capability, frequency regulation, and support with less interfacing power electronics equipment of DC loads and Distributed Energy Resources (DERs) .…”
Section: Introductionmentioning
confidence: 99%
“…2 The design and deployment of the conventional approach of a microgrid are usually done with the help of the Alternating Current (AC) system. 3 The Direct Current (DC) microgrids are gaining attraction in real-time implementation due to various advantages over AC microgrid like lack of need for synchronization, high power transfer capability, frequency regulation, and support with less interfacing power electronics equipment of DC loads and Distributed Energy Resources (DERs). 4 Considering the presence of both AC and DC DERs and loads in a microgrid, hybrid AC/DC microgrid is well capable to provide reliable and economical solutions that can probably eradicate the multistage AC-to-DC or DCto-AC reverse conversions.…”
mentioning
confidence: 99%
“…Existing mathematical models of distribution network configuration involve various design variables that usually include the location [12] and size [13] of equipments like substations and feeders. As the penetration of distributed generation (DG) resources grows, the location and sizing of the DG units has also received increasing attention in the literature (see, e.g., [14], [15], [16], [17]). The network topology is another important design variable (see, e.g., [18], [19], [20], [21]).…”
Section: Introductionmentioning
confidence: 99%